KOMPONEN HERBA VERNONIA CINEREA YANG BERKHASIAT ANTIKANKER - CHOLIES, NOOR
Research is still in progress in many countries to look for anticancer agents from plants or from synthetic compounds. In Indonesia Vernonlacinerea herbs are frequently used in cancer treatment. The purpose of this research is to find out whether this medicinal plant contains any compound having anticancer activity. For this purpose, a cancerous tissue is needed. It has been succesfully developed by injecting benzo(a)pyrene (BP) in the neck of the Muang Thai strain mice. It appeared that the cancerous tissue caused by BP could be succesfully transplanted in other mice of similar strain. The existence of cancer in all of these investigations were proved by histophatological experiments. Further investigation revealed that the cancerous tissues were considerably different from the normal one viz., the 002 of cancerous cells were significantly lower than normal tissues as determined by the Warburg respirometer. Enzymic experiments showed that the specific activities of glutamate oxaloacetate transaminase (POT), glutamate pyruvate transaminase ( CPT) and lactate dehydrogenase (LDH) of cancerous tissues were distinctly lower than those of the normal one. On the other hand no differences in the specific activities of both alkaline and acid phosphatases were observed, Polyacrylamide disc gel electrophoretical experiments revealed that the protein bands of cancerous tissues homogenate as well as the number of LDH Isoenzymes were less than the normal tissues. The appearance of cancer in the neck of mice were accompanied by an increase in specific activities of LDH and GOT in the liver as well as in the blood. Further it was shown that after 90 days of the first injection of the carcinogen the specific activities of blood LDH and GOT appeared to be significantly higher than those in the blood of normal mice, although there was.no sign of cancer appearance yet. In a further experiment, white crystalline solid had been isolated from the herbs of Vernonia cinerea, which was very soluble in water. The melting point was 158Â°C (decomposed). Thin layer, paper as well as high pressure liquid chromatographic analysis showed that the crystals were pure. The isolated compound showed no antibiotical effect on Aspergillus niger or Bacillus megaterium. The intraperitoneal LD50 value in mice was 1 mg/gram. Further the isolated compound appeared to be able to inhibit the activities of GOT, GPT, acid and alkaline phosphatases from the cancerous as well as from the normal tissues. In the course of further examination it was shown that the isolated compound was able to inhibit cancer growth. The elevated levels of GOT and LDH in blood became gradually normal after the treatment with the isolated compound. The evidence of recovery is supported by histophatological experiments. The active component of Vernonia cinerea showed the chemical characteristics of glucoside. Hydrolysis of this compound gave white crystalline aglycone. The molecular formula C 9H803 was assigned on the basis of elemental analysis (C ,= 65. 55%, H = 4.87% and 0 = 29.58%) and molecular weight determination (m/e 164) by mass spectrometry. Its infrared spectrum showed the presence of OH group at about 3250 cm-1, carbonyl lactone at about 1700 cm-1 and C = C double bond at about 1600 cm-l. The ultraviolet data obtained were: AMeOH 258 nm and 212 nm. max The NMR spectrum showed a doublet at 6 5.2. This was characteristic for proton on a cyclic double bond. The triplet at 6 4,3 was the hydroxyl proton. Based on the data obtained so far we suggested the following structur for the aglycone :